Rapid identification and interpretation of gene–environment associations using the new R.SamBada landscape genomics pipeline. (24th June 2019) - Duruz, Solange; Sevane, Natalia; Selmoni, Oliver; Vajana, Elia; Leempoel, Kevin; Stucki, Sylvie; Orozco‐terWengel, Pablo; Rochat, Estelle; Dunner, Susana; ,; ,; Bruford, Michael W.; et al.
Abstract: sam βada is a genome–environment association software, designed to search for signatures of local adaptation. However, pre‐ and postprocessing of data can be labour‐intensive, preventing wider uptake of the method. We have now developed R.SamBada, an r ‐package providing a pipeline for landscape genomic analysis based on sam βada, spanning from the retrieval of environmental conditions at sampling locations to gene annotation using the Ensembl genome browser. As a result, R.SamBada standardizes the landscape genomics pipeline and eases the search for candidate genes of local adaptation, enhancing reproducibility of landscape genomic studies. The efficiency and power of the pipeline is illustrated using two examples: sheep populations from Morocco with no evident population structure and Lidia cattle from Spain displaying population substructuring. In both cases, R.SamBada enabled rapid identification and interpretation of candidate genes, which are further discussed in the light of local adaptation. The package is available in the r CRAN package repository and on GitHub (github.com/SolangeD/R.SamBada). Abstract : see also the Perspective by Manel